2023
DOI: 10.1007/s13278-023-01063-2
|View full text |Cite
|
Sign up to set email alerts
|

Social network analysis of Twitter interactions: a directed multilayer network approach

Abstract: Effective employment of social media for any social influence outcome requires a detailed understanding of the target audience. Social media provides a rich repository of self-reported information that provides insight regarding the sentiments and implied priorities of an online population. Using Social Network Analysis, this research models user interactions on Twitter as a weighted, directed network. Topic modeling through Latent Dirichlet Allocation identifies the topics of discussion in Tweets, which this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Clustering techniques in social network analysis are valuable for discovering groups of individuals with strong ties, revealing social substructures like cliques (Mathematik, 2023), subgroups, or communities. This understanding provides insights into social interactions and helps identify influential individuals or groups (Logan et al, 2023). In molecular biology (Schirra et al, 2023), clustering methods can identify protein communities, aiding the discovery of functional protein groups.…”
Section: Introductionmentioning
confidence: 99%
“…Clustering techniques in social network analysis are valuable for discovering groups of individuals with strong ties, revealing social substructures like cliques (Mathematik, 2023), subgroups, or communities. This understanding provides insights into social interactions and helps identify influential individuals or groups (Logan et al, 2023). In molecular biology (Schirra et al, 2023), clustering methods can identify protein communities, aiding the discovery of functional protein groups.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the model enhances the performance of topic modeling and can effectively capture topic correlation. However, the authors in [11] used LDA to identify the topics of discussion in Tweets, resulting in a directed multilayer network in which users (in one layer) are linked to discussions and topics (in a second layer) in which they contributed, with interlayer connections indicating user participation in discussions. Although there are other methods for topic modeling on short texts, such as the Biterm Topic Model.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, Twitter distinguishes itself from other OSNs as its user base exhibits a distinct focus on real-time communication by sharing thoughts and ideas related to speci c topics rather than prioritizing personal connections (Jain et al, 2021;Logan et al, 2023;Masrom et al, 2021). For example, we selected 150 primary users who had the highest number of likes on their tweets related to a recent topic.…”
Section: Introductionmentioning
confidence: 99%